Exploring Thermospheric Variations Triggered by Severe Geomagnetic Storm on 26 August 2018 Using GRACE Follow‐On Data. Issue 5 (14th May 2020) - Krauss, S.; Behzadpour, S.; Temmer, M.; Lhotka, C.
Abstract: With the successful launch of the satellite mission Gravity Recovery and Climate Experiment (GRACE) Follow‐On in May 2018 the opportunity arises to resume the analysis of accelerometer data regarding space weather induced perturbations of the Earth's thermosphere. On 21 August 2018 a complex interplanetary coronal mass ejections occurred on the Sun, which subsequently triggered an unexpected large geomagnetic storm on 26 August. We present a detailed analysis of the interplanetary coronal mass ejection eruption and explore the occurred perturbation of the neutral mass density in the upper Earth's atmosphere. Due to the heating and the subsequent expansion of the thermosphere also the drag force acting on the spacecraft is enhanced. This leads to an additional storm‐induced orbit decay, which we calculate by means of variations in the semimajor axis. The evaluation is based on the utilization of accelerometer measurements from GRACE Follow‐On. For the reduction of disturbing nongravitational forces we implemented a physical shadow function, which incorporates the Earth's oblateness and the atmospheric refraction and extinction. Additionally, the estimation of Earth's reradiation is now based on hourly measurements by the Clouds and the Earth's Radiant Energy System. The resulting atmospheric densities and orbit decays are compared with predictions from our preliminary thermospheric forecasting tool, which is based on the study by Krauss et al. (2018, https://doi.org/10.1029/2018JA025778 ). The evaluation shows that the maximum estimated orbit decay triggered by the geomagnetic storm on 26 August is in the order of approximately 8.2 m and thus in good accordance with the forecasted value (9.5 m)—predicted with a lead time of about 60 min. Key Points: Evaluation of accelerometer measurements recorded by GRACE Follow‐On Analyzing a geomagnetic storm triggered by a coronal mass ejection from 21 August 2018 Predicting atmospheric densities and satellite orbit decays based on interplanetary magnetic field observations